Indoleamine 2,3-dioxygenase vaccination - Andersen, Mads Hald (Oncoimmunology, 2015)
Indoleamine 2,3-dioxygenase (IDO) is an immunoregulatory enzyme. Remarkably, we discovered IDO-specific T cells that can influence adaptive immune reactions in patients with cancer. Further, a recent phase I clinical trial demonstrated long-lasting disease stabilization without toxicity in patients with non-small-cell lung cancer (NSCLC) who were vaccinated with an IDO-derived HLA-A2-restricted epitope.